Using the 4C/ID model in e-physics modules (e-PMs) towards meaningful learning among PMA cadets - Arnaldo, Russel L. (Animo Repository, 2023)
Advancing Physics instruction in the Academy contributes to attaining the Philippine Military Academy (PMA) mission. Physics courses in the Academy should ensure cadets' Physics instructional needs are addressed by providing appropriate learning environments with relevant content, thus promoting meaningful and proficient learning among cadets. The primary goal of this research is to create and implement online Electronic Physics Modules (e-PMs) for PMA cadets. The e-PMs cover sonar and radar, engines of military vehicles, and military electronics and communications in their PHY353 (Physics) course. The e-PMs are based on the (1) 4C/ID (four-component instructional design) model grounded in Sweller's Cognitive Load Theory and Mayer's Theory of Multimedia Learning, and (2) Meaningful Learning Theory. Furthermore, this research argues that implementing e-PMs in the Academy affects cadets' class performance, level of problem-solving skills, and motivation to learn Physics in PHY353—the parameters of cadets' Physics learning in the Academy. The methodological framework used for the whole study is the ADDIE (analyze, design, develop, implement, and evaluate) instructional system design framework. In determining the impact of the intervention, this research sought to determine the cadets' standings on the three variables before and after using e-PMs. Moreover, it determined whether significant differences existed between each variable's standings before and after the intervention. Finally, it determined whether there was a correlation between these variables following the intervention. This research used a quasi-experimental design. The entire PMA Class of 2023, three hundred twenty-nine (329) Secondclass (third-year) cadets, underwent instruction using the e-PMs in their PHY353, the AY 2021-22. The percentages of the frequency and the mean for the descriptive statistics were used. In contrast, the paired t-test, Mann-Whitney test, Hake gain, Cohen's d, Pearson r correlation, and Path Analysis (SEM) measures were used for the inferential statistics. Significant differences exist between the cadets' before and after intervention (a) class performance, t(251) = -5.229, p =.001), (b) level of problem-solving skills, t(252) =-5.302, p =.001, and (c) motivation to learn Physics, t(252) = -6.669, p =.001. Furthermore, there is a significant linear relationship between cadets' class performance and problem-solving skills in PHY353, r(252) =.93, p =.001. At the same time, there are nonlinear relationships between cadets' problem-solving skills and motivation, r(252) = -.02, p = .756, and between cadets' class performance and motivation, r(252) =.00, p =.944). The e-PMs based on the 4C/ID model can be implemented in the Physics course in the Academy. Cadets performed better in class, improved their problem-solving skills, and were more motivated to learn physics when they had access to online and new learning environments. Strengthening cadets' problem-solving skills in physics is recommended to attain good class performance in PHY353. The Physics courses in PMA should address and respond to the cadets' diverse and varied motivational factors and their impact on cadets' proficient learning and training. In addition, further studies on e-PMs or e-modules based on the 4C/ID model or other IDMs and their use are recommended. Keywords: e-PMs, 4C/ID model, Physics, ADDIE model, PMA Cadets